Hubungan Kebiasaan Menonton Food Vlog dan Peningkatan Nafsu Makan Mahasiswa di Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta - Nita Puspitasari; Luluk Ria Rakhma; Siti Zulaekah (Yayasan Literasi Sains Indonesia, 2025)
Appetite is a natural urge that arises from the body, which can be influenced by physiological and psychological conditions. Food-related content (food vlogs) widely available on social media is believed to be one of the factors that can influence increased appetite, especially among university students. The purpose of this study is to determine whether there is a relationship between the habit of watching food vlogs and increased appetite among students at the Faculty of Health Sciences, Muhammadiyah University of Surakarta. The study employs a quantitative approach with a cross-sectional design. The sampling process uses simple random sampling. Data were collected using a questionnaire on food vlog viewing habits consisting of 15 statements and the FCQ-T (Food Cravings Questionnaire-Trait) questionnaire with 35 statements. Data analysis was conducted using the Spearman Rank test via SPSS software version 20. The questionnaire results indicated that the majority of students had a high food vlog viewing habit (72.2%). However, the majority of students experienced a low increase in appetite (60.8%). Statistical analysis revealed a significant correlation between the two variables with a p-value of 0.003 and a correlation coefficient of r = 0.326. Based on these results, it can be concluded that the more frequently an individual watches food vlogs, the more likely their appetite will increase, although the effect is not overly significant.